KAJIAN GAYA HIDUP HEDONISME MASYARAKAT DESA TATELI TIGA KECAMATAN MANDOLANG KABUPATEN MINAHASA - Doloy, Filki; Tasik, Femmy Femmy C. M. Tasik; Mokalu, Benedicta J. (Universitas Sam Ratulangi, 2020)
In Sociology, social interaction is the key to all social life because without social interaction, there would be no life together. Personal meeting of individuals will not result in social intercourse in a social group. Such associations will only occur if individuals or groups of people work together, talk to each other, and so on to achieve a common goal, create competition, dissension, and so forth. So, it can be said that social interaction is the basis of social processes, which point to dynamic social relations. In the life of the people of the village of Tateli Tiga in general there has been a change in behavior both personally and towards others. This is result of the development of technology and science in society so that people are required to live according to current trends. Tateli village community there of the many people choose to live looking for pleasure without realizing they have shown a hedonic lifestyle. With such a lifestyle giving encouragement to others to follow or try to do a lifestyle that gives pleasure to that person. With a variety of interactions carried out within the community, the lifestyle changes as technology develops. Because it makes they are to know what is becoming a trend among the general public. But in the community of Tateli Tiga village they prefer to lifestyle to developments that exist and they fill their free time with fun activities such as debauchery, drinking and other activities that make them seem to forget all the burden of the problems being faced. Hedonistic lifestyles such as carrying out activities or gatherings by a group of people to be able to fill spare time by partying and drinking.Â Keywords: Hedonism Lifestyle, Village Communities